POSITIVE CORRELATION OF PARENTAL ATTACHMENT AND SELF-CONCEPT IN ADOLESCENTS AT MTS AL-BAITUL QADIM AIRMATA KUPANG - Annisa Jihan Safitri; Putu Indrawan; Muhammad D Pua Upa (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2021)
This study aims to determine the relationship between parental attachment and self-concept in adolescent children. We found that students tended to behave negatively following the behavior of their group rather than following the direction and attention of their parents. This study uses a quantitative approach to the type of correlational research. The results of this study indicate that there is a relationship between attachment and self-concept in MTs Al-Baitul Qadim Airmata Kupang students. It can be concluded that between parental attachment and self-concept in MTs Al-Baitul Qadim Airmata Kupang students there is a strong relationship with a positive direction, meaning that the higher the parental attachment, the higher the self-concept in MTs Al-Baitul Qadim Airmata Kupang students. On the other hand, the lower the parent's attachment, the lower the self-concept in MTs Al-Baitul Qadim Airmata Kupang students.